Patterns of Care and Age Specific Impact of Resection Extent and Adjuvant Radiotherapy in Pediatric Pineoblastoma. (1st September 2019) - Jin, Michael Chuwei; Prolo, Laura M; Wu, Adela; Azad, Tej D; Shi, Siyu; Rodrigues, Adrian; Soltys, Scott G; Pollom, Erqi; Li, Gordon; Hiniker, Susan; Grant, Gerald A
Abstract: INTRODUCTION: Pediatric pineoblastomas are highly aggressive tumors that portend poor outcomes despite multimodal management. While treatment often utilizes a combination of surgical resection, radiotherapy, and chemotherapy, controversy remains regarding optimal disease management. METHODS: A total of 211 pediatric (age 0-17 yr) histologically confirmed pineoblastoma patients were queried from the National Cancer Database, a nationwide, hospital-based registry. Wilcoxon rank-sum statistics and Chi-squared analyses were used to compare continuous and categorical variables, respectively. Univariable and multivariable Cox regressions were used to evaluate prognostic impact of demographic, tumor, and treatment-related covariates. Propensity-score matching was used to balance baseline characteristics. RESULTS: Older patients (age = 4) experienced improved overall survival compared to younger patients (age < 4) (hazard ratio [HR] = 0.41; 95% confidence interval [CI] = 0.25-0.66). Radiotherapy usage was associated with age and socioeconomic factors, with older patients (adjusted odds-ratio [aOR] = 5.21; 95% CI = 2.61-10.78) and those residing in high-income regions (aOR = 3.16; 95% CI = 1.21-8.61) receiving radiotherapy more frequently. Radiotherapy was associated with improved survival after adjusting for covariates in older (HR = 0.31; 95% CI = 0.12-0.87) but not younger (HR = 0.64; 95% CI = 0.20-1.90) patients. Patients receiving either gross total resection (GTR) or subtotal resection (STR) demonstrated greater survival benefits with addition of radiotherapy than patients receiving neither (surgery HR = 0.23; 95% CI = 0.08-0.65; no surgery HR = 0.46; 95% CI = 0.22-0.97). Older patients experienced improved outcomes associated with aggressive resection ( P  = .041); extent of resection was not associated with survival in younger patients ( P  = .880). CONCLUSION: Aggressive resection of pineoblastoma was associated with improved survival only in older patients. Radiotherapy extended survival in patients receiving surgery compared to those receiving neither. Age-stratified approaches might allow for improved disease management of pediatric pineoblastoma.